2002
DOI: 10.1007/s00415-002-0776-3
|View full text |Cite
|
Sign up to set email alerts
|

Normal dopamine transporter binding in dopa responsive dystonia

Abstract: We report the clinical manifestations of dopa responsive dystonia (DRD) in 2 patients from the same family. The brain magnetic resonance images (MRI) were normal. The dopamine transporter (DAT) imaging with (99m)Tc-TRODAT-1 was performed in the 2 probands, 8 patients with young onset Parkinson disease (YOPD) and 16 normal controls. The ratios of (99m)Tc-TRODAT-1 brain SPECT in the striatum were 2.40 +/- 0.12 (right) and 2.30 +/- 0.17 (left) in these 2 DRD patients as compared with 1.38 +/- 0.18 (right), 1.41 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 20 publications
(35 reference statements)
2
18
0
Order By: Relevance
“…Our findings and previous reports have all shown that DRD can be clearly differentiated from EOIP by using an [ 18 F]dopa PET [7, 8, 9]or DAT SPECT scan [3, 4, 5, 6]. Striatal binding of [ 18 F]dopa by using PET is normal or only mildly reduced, and that of DAT ligands labeled with [ 123 I] or [ 99m Tc] by using SPECT are normal in DRD but reduced in EOIP; however, the expense and limited availability of PET preclude its widespread clinical application.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our findings and previous reports have all shown that DRD can be clearly differentiated from EOIP by using an [ 18 F]dopa PET [7, 8, 9]or DAT SPECT scan [3, 4, 5, 6]. Striatal binding of [ 18 F]dopa by using PET is normal or only mildly reduced, and that of DAT ligands labeled with [ 123 I] or [ 99m Tc] by using SPECT are normal in DRD but reduced in EOIP; however, the expense and limited availability of PET preclude its widespread clinical application.…”
Section: Discussionsupporting
confidence: 74%
“…Both dopamine transporter (DAT) single-photon emission computed tomography (SPECT) using [ 123 I]-based or [ 99m Tc]-based ligands and [ 18 F]dopa positron emission tomography (PET) have shown normal or only mildly reduced striatal uptake in DRD and clearly differentiate DRD from EOIP [3, 4, 5, 6, 7, 8, 9]. Dopamine D2 receptor densities are reported to be normal or elevated in DRD patients [10, 11], while [ 123 I]IBZM SPECT or [ 11 C]raclopride PET have shown initial upregulation of striatal dopamine D2 receptors in the contralateral putamen of early-stage idiopathic parkinsonism [12, 13], and normal [12]or reduced [14, 15, 16]D2 receptor densities in fluctuating idiopathic parkinsonism.…”
Section: Introductionmentioning
confidence: 99%
“…99m Tc]TRODAT scan was normal in one patient reported previously [Huang et al, 2002]. The intact dopamine neuron might explain the extremely benign parkinsonian symptoms which were mild and progressed very slowly (20 and 14 years of duration in two patients).…”
Section: Genetic Datamentioning
confidence: 67%
“…There are limited reports about clinical phenotypes and genotypes of DRD among those with Chinese ethnicity from Taiwan and China [Huang et al, 2002;Wu et al, 2008]. The search for large exonic deletions was not mentioned in a recent report [Wu et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Brain 99m Tc-TRODAT-1 SPECT was performed as previously described [15, 16, 17]. The brain 99m Tc-TRODAT-1 SPECT study showed normal DAT functioning at the dopaminergic pathway in the brain parenchyma.…”
Section: Case Reportmentioning
confidence: 99%